SWOT Analysis is Used in the Startup Business Development Strategy - Elda Diah Safitri; Sausan Raihana Putri Junaedi; Ari Priono (Startupreneur Business Digital (SABDA Journal), 2023)
Fast-growing startups in Indonesia have an effect on the economy of the country. The fact that Indonesia is one of the five nations with the most startups in the world attests to the high level of public interest. Numerous firms that have strong financial valuations fall under the category of unicorns or even decacorns. One of the funding options in the capital process, which, of course, cannot be isolated from the company's strategies, is to execute an Initial Public Offering (IPO) on the Indonesia Stock Exchange (IDX). Up till 2022, two startups, PT. Bukalapak.com (BUKA) and PT. Goto Gojek Tokopedia (GOTO), have held initial public offerings. Analyze the two companies' strengths, weaknesses, opportunities, and threats (SWOT) in order to determine their respective business strategies. This study used a descriptive qualitative method, and it collected its data by completing literature reviews from reliable sources of scholarly literature and online news.